Improving the Quality of Public Expenditure in the Dominican Republic - World Bank (Washington, DC, 2017)
This book addresses the achievements, challenges, and opportunities to improve the quality of public spending. Steps to make such changes have come through monitoring and evaluation approaches that can be replicated or expanded; sectoral efforts to improve the performance of priority programs; Congress's use of information on the results of public spending; the implementation of performance budgeting at subnational levels; and the harmonization of accounting between the three levels of the federal government. All these aspects are key elements of comprehensive reform. Currently, as the book states, accountability focuses on achieving results rather than on centering attention on mere compliance with rules and procedures. In this context, based on a new legal framework, the government of Mexico has decisively promoted results-based management and budgeting. The Performance Evaluation System (SED) was finally established in 2008 with the institution of the principles, concepts, methodologies, guidelines, procedures, and systems that support its operation. Its adoption as a common practice in the Federal Public Administration (APF) process will require a gradual, progressive, systematic learning and continuous improvement that should allow performance evaluation to take root in the APF. This calls for consolidating the Results-Based Budgeting (RBB)-SED in all agencies, expanding its use and improving the quality of the information that feeds it. However, not just the APF benefit will from the implementation of the RBB-SED. As the publication suggests, the approach to an expenditure budget based on performance information offers Congress great opportunities to enhance its regulatory and supervisory functions. The improvement in the quality of Matrices de Indicadores para Resultados (MIRs), program evaluations, and their integration into the budgetary programming cycle also contributes to this purpose.